Calculati inQ ecuatiile
7(x+2)-3(x-4)-x=2(x+5)+46=
4x+12-3(x+4)=2(x+5)=
4(x+5)+3(x+3)=2(x+15)+4==
8(x+1)-4(x-3)-x=2(x+18)=
5x+16-4(x+4)=2(x+9)=
5(x+2)+4(x-3)=3(x+8)-14=

1
4x+12-3(x+4)=2(x+5)
4x+12-3x-12=2x+10
x=2x+10
x-2x=10
x=-10
4(x+5)+3(x+3)=2(x+15)+4
4x+20+3x+9=2x+30+4
7x+29=2x+34
7x-2x=34-29
5x=5
x=5:5
x=1
8(x+1)-4(x-3)-x=2(x+18)
8x+8-4x+12-x=2x+36
3x+20=2x+36
3x-2x=36-20
x=16
5x+16-4(x+4)=2(x+9)
5x+16-4x-16=2x+18
x=2x+18
x-2x=18
x=-18
5(x+2)+4(x-3)=3(x+8)-14
5x+10+4x-12=3x+24-14
9x-2=3x+10
9x-3x=10+2
6x=12
x=12:6
x=2

Răspunsuri

2014-10-24T19:23:53+03:00
7(x+2)-3(x-4)-x=2(x+5)+46
7x+14-3x+12-x=2x+10+46
 4x+26=2x+56
4x-2x=56-26
 2x=30
 x=30:2
x=15

 4x+12-3(x+4)=2(x+5)
 4x+12-3x-12=2x+10
 x=2x+10
 x-2x=10
 x=-10

4(x+5)+3(x+3)=2(x+15)+4
 4x+20+3x+9=2x+30+4
 7x+29=2x+34
7x-2x=34-29
5x=5
 x=5:5
x=1

8(x+1)-4(x-3)-x=2(x+18)
 8x+8-4x+12-x=2x+36
 3x+20=2x+36
3x-2x=36-20
 x=16

5x+16-4(x+4)=2(x+9)
5x+16-4x-16=2x+18
 x=2x+18
 x-2x=18
 x=-18 
    
5(x+2)+4(x-3)=3(x+8)-14

 5x+10+4x-12=3x+24-14
 9x-2=3x+10
9x-3x=10+2
 6x=12
 x=12:6
x=2





3 3 3